IMPLIKASI HUKUM ATAS PERUBAHAN KETENTUAN PATEN DAN MEREK DALAM UNDANG-UNDANG CIPTA KERJA - Devica Rully Masrur (Fakultas Hukum, Universitas Warmadewa, 2024)
ABSTRACT This study aims to examine the development of Intellectual Property Rights provisions, especially patents and brands after the enactment of the Job Creation Law, namely Law Number 6 of 2023. The problems studied in this study are about the legal implications of trademark and patent provisions as amended in the Law on Job Creation. The research method used is a normative juridical research method with a statutory approach and a conceptual approach. Changes in provisions in the Job Creation Law related to Patents and Trademarks have positive and negative impacts, among which are beneficial is the opening of the patent and trademark registration process which is easier and does not take a very long time. However, the Job Creation Law has changed the substantial provisions regarding the obligation of patent holders to transfer technology and create jobs have been removed by the Job Creation Law. Although the goal is to accelerate investment, it has serious implications for the alignment of patent benefits for the Indonesian people for technology transfer opportunities and the opening of employment opportunities, among those affected, including Micro, Small and Medium Enterprises.